Comparative study of surface temperature of lithium-ion polymer cells at different discharging rates by infrared thermography and thermocouple. (June 2020) - Rani, M.F.H.; Razlan, Z.M.; Shahriman, A.B.; Ibrahim, Z.; Wan, W.K.
Highlights: Surface temperature of LiPo cells was investigated at different discharging rates. Measurement was taken by thermal imaging camera and thermocouple at different views. Surface temperature distribution, maximum surface temperature, and temperature rise were varied. Infrared thermography measurement is more accurate than thermocouple measurement. Abstract: The objective of this study was to compare the surface temperature of lithium-ion polymer cells at different discharging rates by infrared thermography and thermocouple measurement. The cells were discharged by using a battery workstation at discharging rates of 2.0 A, 4.0 A, 6.0 A, 8.0 A, and 10.0 A in a controlled testing condition. This study focused on surface temperature distribution, maximum surface temperature, and temperature rise evolution. Higher discharging rate generates more heat in LiPo cells, which causes larger temperature gradient, higher maximum surface temperature, and higher temperature rise. During the discharging process, non-uniformity spatial distribution of LiPo cells was observed. No critical surface temperature was observed when reaching towards the end of discharging process as the surface temperature distribution managed to become spatially uniform. Most of the maximum surface temperatures were spotted at the lower part of the LiPo cells. In addition, the captured infrared (IR) images found that the temperature rises rapidly at higher discharging rates. In comparison, surface temperature measurement by infrared thermography provided higher accuracy than thermocouple. The findings of this study provide evidences in better development of battery thermal management systems with consideration of surface temperature distribution and temperature rise.